Regenerative stem cell therapy for stroke in Europe (RESSTORE): a multicenter randomized controlled efficacy clinical trial - Legris, Loïc; Moisan, Anaick; Jaillard, Assia; Bonnet, Louise; Moulin, Thierry; Sibon, Igor; Touzé, Emmanuel; Favre-Wiki, Isabelle; Cordonnier, Charlotte; Dellaschiava, Lucie; Mazighi, Mikael; Rosso, Charlotte; et al. (Frontiers in Stroke, 2024)
Introduction: Encouraging the activation of brain repair mechanisms and fostering spontaneous functional recovery in stroke patients holds great promise for alleviating the global burden of this condition, allowing an extended therapeutic time window. Cell-based regenerative therapy (with mesenchymal stem/stromal cells, such as Adipose Derived Stem Cells, ADSCs) is particularly attractive considering an excellent safety profile, low immunogenicity after allogeneic application and well-established functional benefits on stroke recovery in animal models. The aim of this study is to assess efficacy and safety effects of intravenous (IV) infusion of fresh cultured allogeneic ADSCs on recovery after ischemic stroke. Population and Methods: RESSTORE is a multicentric, randomized 1:1, controlled, double-blind clinical trial (RCT). Eighty patients will be enrolled in 9 French stroke centers. Main inclusion criteria are: ≥ 18-year-old, acute hemispheric ischemic stroke, NIHSS ≥ 7 including motor score ≥ 3. According to the previous dose-escalation safety trial data, the maximum tolerated dose of 3 million ADSCs /kg was selected. IV infusion is performed within 10 days following stroke onset, with a follow-up over 2 years. Outcomes: The primary endpoint is the motor NIHSS subscore, computed as the sum of upper limb, lower limb and hand scores, measured 6 months after stroke onset to assess motor recovery. The secondary outcomes are the occurrence of death / serious adverse events, clinical scores (detailed NIHSS, MoCA, mRS, Aphasia Handicap Score, Depression Intensity Scale Circles, Fatigue Scale…), immunomonitoring (for 30 first patients) and multimodal biomarkers derived from diffusion and functional MRI. Discussion: This study may provide some evidence for the effects of fresh cultured allogenic ADSCs IV infusion in subacute stroke that may help to design a larger international RCT.